Analysis Of Management Of Performance Allowances For Literary Staff At The University Of Education Indonesia - Purwadiansyah, Aan; Adji, Wilman Zuarko (JAKI : Jurnal Akuntansi, 2025)
This study analyzes the management of performance allowances for educational staff at the Faculty of Language and Literature Education (FPBS), Indonesian Education University (UPI). Performance allowance is additional compensation based on work achievement, designed to boost motivation, productivity, and overall organizational performance. While this allowance is crucial for improving productivity, accountability, and the quality of administrative services, its implementation at FPBS UPI faces challenges. These challenges include a low understanding of indicators, a lack of transparency in evaluation, and suboptimal use of information technology. Such obstacles can hinder the achievement of objectives and lower employee motivation and satisfaction. Using a descriptive quantitative approach through observation and interviews, this study aims to describe the current state of performance allowance management. The results indicate that the management of performance allowances is considered relatively good by employees. The majority of employees understand the performance indicators, perceive the evaluation mechanism as transparent, and feel the efficiency benefits of information technology. However, improvements are still needed in system communication and complaint procedures. The findings are expected to provide a comprehensive overview of the performance allowance system's implementation and its success factors